Skin color and investment performance in South Africa's mutual funds industry - Chekenya, Nixon S.; Sikomwe, Shingirai (Emerald Group Holdings Ltd., 2021)
Purpose Using data for the period 1965–2016, we investigate whether there are systematic differences between the investment performance of Black fund managers and those of other races in South Africa and whether investors recognize these differences. The two-tailed test results show that there is no significant difference between the two means considering the 12 months yield return at a hypothesized mean difference of zero. There is no statistical difference at 5% level of significance implying that the performance of Black fund managers is as equally as that of managers of other races. Our results also show that the percentage of Black fund managers in South Africa is still too low even as the workforce gets diverse. There's no single explanation for what is happening in this industry. The findings cannot be explained by differences in fund characteristics such as age, total assets under management or expenses or from the performance lenses. The results seem hard to reconcile with an explanation of differences in portfolio characteristics such as return volatility or market, size, value and momentum exposures.